Measurement of Surface Damage through Boundary Detection: An Approach to Assess Durability of Cementitious Composites under Tannery Wastewater - Tanvir Manzur; Khaled Mahmood Ehsan; Sinha Lamia Sultana; Samira Mahmud (Advances in Materials Science and Engineering)
Concrete structures are often subjected to aggressive aqueous environments which consist of several chemical agents that can react with concrete to produce adverse effects. A Central Effluent Treatment Plant consisting of reinforced concrete structures which is being constructed at Savar, Bangladesh, is an example of such a case. The purpose of this treatment facility is to reduce the environmental pollution created by tannery wastewater. However, tannery wastewater consists of several chemicals such as sulfates, chlorides, and ammonium, which, from the literature, are known to generate detrimental effects on concrete. Evaluation of durability of concrete structures in such environments is therefore imperative. This paper highlights a technique of boundary detection developed through image processing performed using MATLAB. Cement mortar cubes were submerged in simulated tannery wastewater and the images of the surface of cubes were taken at several time intervals. In addition, readings for compressive strength and weight were also taken on the same days. In this paper, an attempt is made to correlate the results from image processing with that of strength and weight loss. It was found, within the scope of this study, that the specimens which suffered greater strength and weight loss also underwent greater loss of surface area.